The regulation effect of EGCG3''Me phospholipid complex on gut flora of a high‐fat diet‐induced obesity mouse model. Issue 7 (7th May 2019) - Lin, Yuhai; Zhang, Xin; Cheng, Lu; Yang, Hua
Abstract: Despite the remarkable bioactivity, the potential of EGCG3''Me to be fully utilized has not yet been completely elucidated due to its low absorption. It has been reported that phospholipids can act as agents to improve the absorption of antioxidants. Therefore, EGCG3''Me phospholipid complex (EPC) was utilized in this study to investigate its activity on gut flora of an obesity mouse model. After the administration of the complex for 8 weeks, the relative abundance of Bacteroidetes was significantly increased ( p  < 0.05); meanwhile, the relative abundance of Firmicutes was decreased, suggesting the potential anti‐obesity effect of the complex. Furthermore, the expression of Muc2 and Reg3g were directly upregulated by EPC intervention. Practical applications: Although EGCG3''Me has shown excellent biological benefits, the presence of multiple hydroxyl groups and high polar properties hindered its application. This study indicated the potential of phospholipids in promoting the bioavailability of EGCG3''Me and might contribute to the production of functional food with better tea catechins absorption.